Carbothermal Shock Synthesis of High Entropy Oxide Catalysts: Dynamic Structural and Chemical Reconstruction Boosting the Catalytic Activity and Stability toward Oxygen Evolution Reaction. Issue 35 (27th July 2022) - Abdelhafiz, Ali; Wang, Baoming; Harutyunyan, Avetik R.; Li, Ju
Abstract: Mixed transition‐metals (TM) based catalysts have shown huge promise for water splitting. Conventional synthesis of nanomaterials is strongly constrained by room‐temperature equilibria and Ostwald ripening. Ultra‐fast temperature cycling enables the synthesis of metastable metallic phases of high entropy alloy nanoparticles, which later transform to oxide/hydroxide nanoparticles upon use in aqueous electrolytes. Herein, an in situ synthesis of non‐noble metal high entropy oxide (HEO) catalysts on carbon fibers by rapid Joule heating and quenching is reported. Different compositions of ternary to senary (FeNiCoCrMnV) HEO nanoparticles show higher activity towards catalyzing the oxygen evolution reaction (OER) compared to a noble metal IrO2 catalyst. The synthesized HEO also show two orders of magnitude higher stability than IrO2, due to stronger carbide‐mediated intimacy with the substrate, activated through the OER process. Alloying elements Cr, Mn and V affect OER activity by promoting different oxidation states of the catalytically active TM (Fe, Ni and Co). Dissolution of less stable elements (Mn, V and Cr) leads to enhancements of OER activity. Dynamic structural and chemical perturbations of HEO oxide nanoparticles activate under OER conditions, leading to enlargement in ECSA by forming mixed single atom catalysts and ultra‐fine oxyhydroxide nanoparticles HEOs. Abstract : In situ structural and morphological perturbations that occur during an electrocatalytic reaction process, yield an ever‐improving catalyst, and an exceptionally intimate interaction with catalyst‐support for ultra‐prolonged operations. A revolutionary nanomaterials synthesis strategy overcomes thermodynamic governing rules, produces novel chemistries at a millionfold greater throughput rate than conventional methods.